Fatih Camii at Enez and the Cathedrals of the Middle Byzantine Period - Maltseva, Svetlana V.; Freze , Anna A. (Actual Problems of Theory and History of Art, 2024)
Fatih Camii at Enez is traditionally considered to be a part and parcel of the Constantinopolitan architectural school. However, its construction date and role in the history of Byzantine architecture are still debated. Recent architecture-archaeological studies of the monuments erected during the 11th century with assistance of the Constantinopolitan master builders allow to suggest that the cathedral at Enez may have been built in the same time period, possibly, in the first half – middle of the 11th century. The revised data of the dendrochronological analysis of the examples taken from Fatih Camii also testify in favor of the given decades. Certain constructional, technological, compositional and decorative characteristics of Fatih Camii find their closest parallels in two monuments: the katholikon of Nea Moni on Chios and the cathedral of St. Sophia in Kiev. Both churches were built in the 1030s–1040s. The church in Nea Moni shares with Fatih Camii a similar set of decorative elements executed in brick and similar location on the façades, as well as the final treatment of the walls with incised plaster coating, imitating regular masonry. Moreover, the cathedral in Kiev has an analogous layout and constructional characteristics, such as an elongated western part of the naos without additional eastern bays and lowered arches, supporting the dome.This study is based on the research supported by the Program of Fundamental Research of the Ministry of Construction, Housing and Utilities of the Russian Federation and of the Russian Academy of Architecture and Construction Sciences — 2024, research project 1.1.1.1.
Keywords: Fatih Camii at Enez; Byzantine architecture; Constantinople; Thrace; church architecture